2020
DOI: 10.2174/1389203721666191231105546
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Fungal Components by the Host Immune System

Abstract: : By being the first point of contact of the fungus with the host, the cell wall plays an important role in the pathogenesis, having many molecules that participate as antigens that are recognized by immune cells, and also that help the fungus to establish infection. The main molecules reported to trigger an immune response are chitin, glucans, oligosaccharides, proteins, melanin, phospholipids, and others, being present in the principal pathogenic fungi with clinical importance worldwide, such as Histoplasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 189 publications
0
7
0
Order By: Relevance
“…In addition, the heteroglycan used in this study was composed of chitin, mannan, and glucan. These polysaccharides could be recognized by PRRs and thus activated macrophages, including increased PRR expression and chitinase secretion, which might promote fungal phagocytosis in previous studies [ 16 ]. For example, Barbara et al reported that chitin upregulated TLR2 and TLR4 transcription in keratinocytes [ 26 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the heteroglycan used in this study was composed of chitin, mannan, and glucan. These polysaccharides could be recognized by PRRs and thus activated macrophages, including increased PRR expression and chitinase secretion, which might promote fungal phagocytosis in previous studies [ 16 ]. For example, Barbara et al reported that chitin upregulated TLR2 and TLR4 transcription in keratinocytes [ 26 ].…”
Section: Discussionmentioning
confidence: 98%
“…The fungal cell wall is composed of many polysaccharides that can be recognized by immune cells, regulate cytokine secretion, and modulate immune responses [ 16 , 17 ]. The culture media, growth conditions and drug treatment may impact fungal morphologies and cell wall composition [ 11 , 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PAMPs stimulate a host-specific immune response directed at eliminating the pathogen from the host. Chitin is a major fungal PAMP and the ability of chitin to induce an immune response relies on several factors, such as its source, size, and concentration [ 202 , 203 , 204 ]. Chitin can interact with pattern recognition receptors (PRRs) present on immune cells and is recognized by TLR2, Dectin-1 and mannose receptors (MR).…”
Section: Chitin and Host Immune System Interactionmentioning
confidence: 99%
“…Any component of the cell wall could be a potential PAMP. It is reported that the main molecules that trigger the immune response are chitin, β-glucan, mannan and others ( 13 ).…”
Section: Fungi Recognition Receptors On Mcsmentioning
confidence: 99%